Expected Time to Recruitment for a Three Grade Manpower System with Bivariate Policy of Recruitment Using Geometric Process for Inter Decision Times - Samundeeswari, D; Vidhya, S; Chitra Kalarani, T (International Journal of Engineering and Technology, 2018)
In this paper the time to recruitment is studied using bivariate max policy of recruitment for a three grade manpower system with attrition generated by its policy decisions. It is assumed that the threshold distribution for all the three grades is exponential and the inter decision times forms geometric process. The analytical results are substantiated with numerical illustration.Â